2010
DOI: 10.1103/physreve.82.026402
|View full text |Cite
|
Sign up to set email alerts
|

Standard map in magnetized relativistic systems: Fixed points and regular acceleration

Abstract: We investigate the concept of a standard map for the interaction of relativistic particles and electrostatic waves of arbitrary amplitudes, under the action of external magnetic fields. The map is adequate for physical settings where waves and particles interact impulsively, and allows for a series of analytical result to be exactly obtained. Unlike the traditional form of the standard map, the present map is nonlinear in the wave amplitude and displays a series of peculiar properties. Among these properties w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
24

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 24 publications
0
22
0
24
Order By: Relevance
“…[32], we studied the regular acceleration experienced by the particle in the region of low action I < 0.20. However, it is also possible to coherently accelerate the particle in regions of higher action as can be seen in Fig.…”
Section: Analytical and Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32], we studied the regular acceleration experienced by the particle in the region of low action I < 0.20. However, it is also possible to coherently accelerate the particle in regions of higher action as can be seen in Fig.…”
Section: Analytical and Numerical Resultsmentioning
confidence: 99%
“…[32], suppose a relativistic particle with charge q, mass m, and canonical momentum p moving under the combined action of a uniform magnetic field B = B 0ẑ and a stationary electrostatic wave of wave vector k, period T , and amplitude ε/2 lying along the x axis. The transversal dynamics of this system is described by the Hamiltonian,…”
Section: Description Of the Systemmentioning
confidence: 99%
“…onde T λé o período de modulação e εé a intensidade dos impulsos (perturbação) ao longo do eixo x. Desta maneira, toda vez que t = kT λ com k ∈ Z, a perturbaçãoé ativada por um instante infinitesimalmente pequeno. Deste modo, a dinâmica transversal deste sistemaé descrita pelo Hamiltoniano [18][19][20]…”
Section: Modelounclassified
“…The difficulty in deriving such maps is that while in the absence of a background magnetic field the canonical variables appear separately in different parts of the Hamiltonian-the momentum in the kinetic part only and the coordinate in the interacting part only-the presence of the magnetic field mixes the variables in the different parts * thalestr@gmail.com of the Hamiltonian, making the integration along one wave period more cumbersome. Only recently it has been shown that by using a set of appropriate canonical transformations one can derive an exact relativistic map that also includes a background magnetic field perpendicular to the direction of the wave propagation [19]. The map led to analytical estimates on the necessary conditions to generate efficient regular acceleration.…”
Section: Introductionmentioning
confidence: 99%
“…[19] by allowing the wave to propagate at an arbitrary angle with respect to the magnetic field. In this case the wave drives the particle dynamics in both the transverse and the parallel direction with respect to the magnetic field, increasing the number of degrees of freedom in the system.…”
Section: Introductionmentioning
confidence: 99%